Financial Risk Management: When Does Independence Fail? - Landier, Augustin; Sraer, David; Thesmar, David (American Economic Review, 2009)
The recent turmoil on credit markets has drawn attention to the risk management function. On many trading oors around the world, traders have been writing insurance against rare events: examples include keeping long positions on CDO tranches or selling protection against default (CDS). In normal times, it is the role of risk management to ensure that the received insurance premia are not entirely considered as income, and that enough capital is set aside to protect the institution against the risk that it is taking. In the period that led to the current crisis, however, risk management has failed to play this role.1 This is particularly troubling as the nance industry is one that has embraced the notion of using counter-powers to limit risk and the importance of dissent within organizations. For instance, the Head of Risk Management at KfW, a German bank, argued for the superiority of having a central risk management function, independent of the business units: The great advantage [of central risk management] is the absence of conict of interest. The central risk management is not driven by the market. We look at the business from a different angle; we are not involved at the personal level. (quoted by PriceWaterHouseCoopers, 2007). The purpose of this paper is to study when such virtuous organizational design may fail. We rst propose a model of risk management. Following Augustin Landier et al (forthcoming), we model the trading oor as a simple hierarchy. The role of the trader (T) is to select an asset to invest in, while the risk manager (RM) can decide to approve, or not. Due to his